2020
DOI: 10.1021/acs.inorgchem.0c02196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glutathione and Histidine on NO Release from a Dimeric Dinitrosyl Iron Complex (DNIC)

Abstract: Rates of NO release from synthetic dinitrosyl iron complexes (DNICs) are shown to be responsive to coordination environments about iron. The effect of biologically relevant cellular components, glutathione and histidine, on the rate of NO release from a dimeric, “Roussin’s Red Ester”, DNIC with bridging μ-S thioglucose ligands, SGlucRRE or [(μ-SGluc)­Fe­(NO)2]2 (SGluc = 1-thio-β-d-glucose tetraacetate), was investigated. From the Griess assay and X-band EPR data, decomposition of the product from the histidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Further therapeutic DNICs were applied to smooth muscle cells to encourage vascular relaxation and contraction by Darensbourg and Lim. They demonstrated that thiophenolate- and thioglucose-bridged, dinuclear DNICs, [(μ-SPh) 2 Fe 2 (NO) 4 ] ( 184 ) and [μ-(SGlu) 2 Fe 2 (NO) 4 ] ( 199 ), release NO to the cytosol of smooth muscle cells with limited cytotoxity and immunotoxicity over 24 hours, without disrupting the cell’s natural processes. ,, …”
Section: Dinitrosyl Iron Complexes (Dnics)mentioning
confidence: 99%
“…Further therapeutic DNICs were applied to smooth muscle cells to encourage vascular relaxation and contraction by Darensbourg and Lim. They demonstrated that thiophenolate- and thioglucose-bridged, dinuclear DNICs, [(μ-SPh) 2 Fe 2 (NO) 4 ] ( 184 ) and [μ-(SGlu) 2 Fe 2 (NO) 4 ] ( 199 ), release NO to the cytosol of smooth muscle cells with limited cytotoxity and immunotoxicity over 24 hours, without disrupting the cell’s natural processes. ,, …”
Section: Dinitrosyl Iron Complexes (Dnics)mentioning
confidence: 99%
“…It has been reported that the NO release ratio is dependent on the chemical structure of the donor itself and the chemical environment . Therefore, we believe that modification of NO donor structures by various groups will affect the release amount of NO. , …”
Section: Introductionmentioning
confidence: 91%
“…31 Therefore, we believe that modification of NO donor structures by various groups will affect the release amount of NO. 32,33 In view of the above, different electron-donating and electron-withdrawing groups such as methyl, chloro, and bromo groups on the aromatic ring were selected to optimize the structure of H1. By detecting NO contents under both normoxia and hypoxia, the NO release ratio of the resulting NO donor compounds with a hypoxia-activating moiety was assayed under hypoxia.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Derived from nitrosylation of a labile iron pool (LIP) or iron–sulfur (Fe–S) clusters, a dinitrosyl iron unit (DNIU) [Fe­(NO) 2 ] was identified as a natural metallocofactor for storage and transport of NO. Inspired by the endogenous DNIU anchored in the protein-bound or low-molecular-weight form, synthetic dinitrosyl iron complexes (DNICs) were explored for controlled delivery of NO and biomedical applications to anti-aging, hypertension, tissue regeneration, diabetic/bacteria-infected wound healing, neurodegenerative diseases, and cancer therapy. In particular, a pioneered study on the photochemistry of dinuclear DNICs [(NO) 2 Fe­(μ-SR)­Fe­(NO) 2 ] discovered the light-responsive release of NO, whereas the utilization of UV/visible/near-infrared (NIR) light can be regulated by the side chain of bridging thiolate ligands. Dinuclear DNICs [(NO) 2 Fe­(μ-SCH 2 CH 2 OH)­Fe­(NO) 2 ] ( DNIC-OH ) and [(NO) 2 Fe­(μ-SCH 2 CH 2 COOH)­Fe­(NO) 2 ] ( DNIC-COOH ) are stable under dark and anaerobic conditions. , Upon incubation of DNIC-OH / DNIC-COOH in a neutral aqueous buffer solution under aerobic conditions, oxidation of bridging thiolate ligands into released disulfide weakens the Fe-to-NO π-back bonding interaction and induces the release of NO, which was indirectly evidenced by the colorimetric Griess reagent or fluorescence probes (Scheme S1). ,, A magnetic-responsive NO-release material (MagNORM) was reported through conjugation of [(NO) 2 Fe­(μ- S -thioglycerol)­Fe­(NO) 2 ] ( DNIC-TG ) with Fe 3 O 4 , followed by encapsulation within thermoresponsive PLGA.…”
Section: Introductionmentioning
confidence: 99%